Concluding results from the first phase of the Zurich Unexpected Difficult Airway course based on exercise of technical skills. (May 2014) - Biro, P.; Grande, B.; Kind, S. L.; Spahn, D. R.; Theusinger, O. M.
Summary We analysed the results of the first phase of the Zurich Unexpected Difficult Airway course. Two hundred and twenty‐eight staff members performed a total of 2712 standardised airway rescue procedures with four airway devices: SensaScope™, LMA Fastrach™, Laryngeal Tube and needle cricothyrodotomy. Four consecutive attempts were performed using each device. We analysed the success rate and the time needed for successful completion for each attempt and device. The success rates and mean (SD) completion times for all participants were 96.2% and 30.2 (15.3) s for the SensaScope, 88.1% and 40.4 (17.2) s for the LMA Fastrach, 99.0% and 12.1 (10.6) s for the Laryngeal Tube and 99.0% and 12.3 (6.1) s for needle cricothyroidotomy. The learning curves resulting from the four consecutive attempts with each device showed a clear pattern of improvement. This institutional airway training course represents a promising method to improve the capability of practitioners to cope with unexpected difficult airway situations.